Double bind the Muslim Right, the Anglo-American left, and the universal human rights - Tax, Meredith (Centre for Secular Space, 2012)
"In a period of right wing attacks on Muslims - or people thought to be Muslims - how does one respond to human rights violations by the Muslim Right without feeding hate campaigns? When US diplomats invoke the oppression of Muslim women to sanctify war, how do we practice feminist solidarity without strengthening Orientalism and neocolonialism? When the US targets jihadis for assassination by drone, should human rights defenders worry about violations perpetrated by those same jihadis or focus on violations by the state? These are some of the questions raised in Double Bind: the Muslim Right, the Anglo-American Left, and Universal Human Rights ... Taking the UK organization Cageprisoners as an example, it shows how to distinguish between organizations that stand for universal and inseparable human rights, and those that use the language of human rights for other purposes. It discusses "five wrong ideas about the Muslim Right" : that it is anti-imperialist; that "defence of Muslim lands" is comparable to national liberation struggles; that the problem is "Islamphobia"; that terrorism is justified by revolutionary necessity; and that any feminist who criticises the Muslim Right is an Orientalist ally of US imperialism."--Publisher description.